2012
DOI: 10.1371/journal.pone.0030001
|View full text |Cite
|
Sign up to set email alerts
|

Visual Lateralization in Wild Striped Dolphins (Stenella coeruleoalba) in Response to Stimuli with Different Degrees of Familiarity

Abstract: BackgroundApart from findings on both functional and motor asymmetries in captive aquatic mammals, only few studies have focused on lateralized behaviour of these species in the wild.Methodology/Principal FindingsIn this study we focused on lateralized visual behaviour by presenting wild striped dolphins with objects of different degrees of familiarity (fish, ball, toy). Surveys were conducted in the Gulf of Taranto, the northern Ionian Sea portion delimited by the Italian regions of Calabria, Basilicata and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 30 publications
4
27
0
Order By: Relevance
“…This type of analysis does not allow estimation of individual preferences, but is often used to assess the one-sided behavioural biases at the population level (Bourne and Todd, 2004;Siniscalchi et al, 2012;Karenina et al, 2017). The first observation of lateral trunk use from each individual was included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This type of analysis does not allow estimation of individual preferences, but is often used to assess the one-sided behavioural biases at the population level (Bourne and Todd, 2004;Siniscalchi et al, 2012;Karenina et al, 2017). The first observation of lateral trunk use from each individual was included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…; wild striped dolphins, Stenella coeruleoalba : Siniscalchi et al. ). It has also been used to show that birds can express social preferences (rooks, Corvus frugilegus : Bird & Emery ), look longer at biological relevant stimuli than basic stimuli (European starlings, Sturnus vulgaris : Tyrrell et al.…”
Section: The History and Implementation Of Looking Time Paradigmsmentioning
confidence: 99%
“…Blois‐Heulin, Crevél, Böye, and Lemasson () have found that bottlenose dolphins use the right eye to observe very unfamiliar objects, but use the left eye to observe familiar objects. Siniscalchi, Dimatteo, Pepe, and Quaranta () also found a right eye preference for viewing unfamiliar objects and noted that these studies of the familiar/unfamiliar dimension in dolphins thus seem to show a deviation from the tendency otherwise noted in vertebrates for the right eye to be favored for familiar stimuli while the left eye is favored for unfamiliar stimuli (see Vallortigara & Rogers, ).…”
Section: Asymmetrical Behavior In Marine Mammalsmentioning
confidence: 87%
“…It could perhaps be argued that the putative right eye advantage for the captive bottlenose dolphins in visual processing, discussed earlier, might be involved, in this case, for surveillance of the edge of the pool. Siniscalchi et al (2012) have even argued that "the right-side down bias" in gray whales (Kasuya & Rice, 1970) humpback whales (Clapham et al, 1995) and bottlenose dolphin fish beaching (Hoese, 1971;Rigley et al, 1981;Silber & Fertl, 1995) could all be the result of the right eye/left hemisphere bias reported by Kilian et al (2005) and other studies referred to earlier, including their own. This may be possible under good viewing conditions, such as exist for swimming in a pool or for surface feeding in clear water.…”
Section: Comparison Of Marine Mammal and Human Asymmetriesmentioning
confidence: 93%